BEYOND THE MONOLITH: COMPREHENSIVE STRATEGIES FOR ARCHITECTING, SCALING, AND SUSTAINING RESILIENT DISTRIBUTED SYSTEMS - Srinivas Chippagiri; Nikhil Kassetty, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The rapid evolution of distributed systems has transformed the way applications are architected, scaled, and sustained. This paper examines the transition from monolithic architectures to scalable and resilient distributed systems. It identifies key challenges such as fault tolerance, data consistency, and scalability bottlenecks, and proposes comprehensive strategies to address these issues. Leveraging advancements in microservices, serverless computing, and AI-driven optimization, this study outlines frameworks for building robust systems capable of meeting modern scalability and performance demands. The paper also highlights emerging trends, including edge computing and IoT integration, offering insights into future research directions.